#### Answer

Infinitely many solutions

#### Work Step by Step

$y=3x-27$
$x-1/3y=9$
$-3*(x-1/3y=9)$
$-3x +y = -27$
$y=3x-27$
$-3x +y = -27$
$(3x-27)+(-3x+y) =y-27$
$3x-27-3x+y=y-27$
$y-27 = y-27$ (true for all real numbers)

Chegg costs money, GradeSaver solutions are free!

Published by
Prentice Hall

ISBN 10:
0133500403

ISBN 13:
978-0-13350-040-0

Infinitely many solutions

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.